Effect of Brainstorming and Expertise on Fraud Risk Assessment - Mohd-Nassir, Mohd-Daniel; Mohd-Sanusi, Zuraidah; Ghani, Erlane K. (International Journal of Economics and Financial Issues, 2016)
The purpose of this study is to examine the direct and interaction effects of brainstorming and auditors' expertise on fraud risk assessment. This study is motivated by the need to improve the government auditors' performance while maintaining high audit quality and increasing public confidence. The inability of the government auditors to detect a misstatement, particularly on the fraud risk may expose auditors to lawsuits which consequently lead to their bad reputation to the public. A 2 X 2 factorial design was employed using 151 government auditors as participants in this study. The results show that brainstorming and auditors' expertise impact the performance of the government auditors on fraud risk assessment. The results also show a significant interaction between brainstorming and auditors' expertise on the government auditors on fraud risk assessment. The findings of this study provide insights on the importance of brainstorming for government auditors with diverse expertise. Keywords: Fraud Risk Assessment, Tests of Controls, Brainstorming, and Auditor' Expertise JEL Classifications: M4, G3, H8